Grain and Seed Proteins Functionality - Carlos Jimenez-Lopez, Jose (IntechOpen, 2021)
Climate resilience and growing population are the two main global challenges that encourage the development of an affordable and sustainable source of vegetable protein to ensure future food security. Advanced scientific programs and agro-food developments should be proprietarily on-demand to face different stresses in order to maintain yield and quality of seed production. In this regard, legume crops are key sustainable alternatives for healthier diets while contributing to appropriate natural resource management. Taken together, the 11 chapters in this book represent a generous addition to the progress in our understanding of climate-resilient legumes, hoping to contribute to the improvement of global food security in the future.